Indeks Kepuasan Publik Bidang Pariwisata dan Strategi Pengembangan Pariwisata di Wilayah Priangan Timur - Firmansyah, Muhamad Ferdy; Nasution, Fatimah Zahra (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2020)
Tourism development is inseparable from supporting public policies where the quality of public management is one of the supporting factors for tourism development in a certain area. Meanwhile, tourism activities contribute and support revenues for local and central governments through taxes and the economic benefits they generate. This study aims to evaluate the effectiveness of public management in tourism by raising a case study in the East Priangan region, West Java Province, namely the City of Tasikmalaya, Tasikmalaya District and Ciamis District. This research uses quantitative methods with a tourism consumer survey approach and a survey of renewable concepts to be applied by public policy stakeholders in tourism development in the East Priangan region. The result, survey A got a score of 27.56988 or at grade